Integration of smart parking in distributed ITS architecture - Alam, Muhammad
In this paper, a new architecture has been proposed to enable distributed sensing in intelligent transportation system (ITS) and to facilitate the transition of legacy systems by the use of gateways (GW) which provide the existing systems with their native interface while also implementing the new functions for local communication and intelligence. The prompt detection of smart parking events are reported by the pervasive wireless sensor network and coordinated by the deployed gateways, drivers are informed in real-time about the situation available services on their route to destination. This contributes to reduce destination time as well as the fuel consumption of each driver and therefore CO2 emissions. In addition, the provision of real-time information on parking availability will help drivers to park their vehicles in less time, thus relieving traffic congestion, reducing CO2 emissions and improving urban mobility. The smart parking sensors are deployed and results are obtained to validate the proposed architecture.